THE CONSTRUCTION OF ADOLESCENT MASCULINITY BY VISUALLY IMPAIRED ADOLESCENTS - Joseph, Lee; Lindegger, Graham (PINS-Psychology in Society, 2025)
This study investigates the intersection of gender and disability in adolescent males with visual impairments. Connell’s seminal work on masculinity which gives particular attention to the notion of hegemonic masculinity, particularly informs this study. The study uses a combined method based on social constructionism and psychoanalysis to investigate visually impaired boys construction of masculinity, how they position themselves in relation to these constructions, and the challenges they experience and strategies they use to maintain a viable masculine identity. The findings show that the construction of masculinity largely reflects that by non-disabled boys. While most of the narratives of these boys show an attempt to align themselves with hegemonic standards of masculinity, there is also evidence of considerable anxiety due to their awareness of their difficulty in performing masculinity according to these expectations. Various discursive strategies to cope with this difficulty are identified. The study reflects some of the limitations of Connell’s notion of hegemonic masculinity.